Plumbagin Enhances the Anticancer Effects of PF Chemotherapy via Downregulation of the PI3K/AKT/mTOR/p70S6K Pathway in Human Tongue Squamous Cell Carcinoma. (13th February 2023) - Pan, Shu-Ting; Ye, Fang-Fei; Huang, Gan; Qiu, Jia-Xuan
Abstract : Cisplatin plus 5-fluorouracil (PF) is used as the standard neoadjuvant chemotherapy (also called preoperative chemotherapy) in the treatment of tongue squamous cell carcinoma (TSCC). Although PF chemotherapy reduces the distant metastasis of TSCC, the five-year survival rate has not significantly improved. In recent years, components considered in traditional Chinese medicine have been researched as adjuvant drugs for radiotherapy and chemotherapy. Plumbagin (PB) is a quinone component isolated from Plumbago zeylanica L. Notably, PB demonstrates numerous anticancer properties. In order to examine the chemosensitization effect of PB on PF and its associated mechanisms, in vitro experiments using TSCC Cal27 and cisplatin (CDDP)-resistant Cal27/CDDP cells were carried out in the present study, and the results were subsequently verified using nude mice xenografts. Results of the present study demonstrated that PB enhanced the anticancer effects of PF on the proliferation, migration, and invasion of Cal27 and Cal27/CDDP cells. Cell cycle assays demonstrated that both Cal27 and Cal27/CDDP cells were arrested in the S phase following the combined treatment of PF and PB. Moreover, the PF and PB combination group induced higher levels of apoptosis in Cal27 and Cal27/CDDP cells compared with the group treated with PF alone. In addition, the results of the present study demonstrated that combined PB and PF inhibited the PI3K/AKT/mTOR/p70S6K pathway in TSCC cells. Moreover, the weight and volumes of tumors in nude mice were reduced following treatment with a combination of PF and PB. Results of the present study also demonstrated that the expression levels of Ki67 were markedly reduced in the combined treatment group compared with the group treated with PF alone. In summary, the results of the present study demonstrated that PB enhanced the PF sensitivity of TSCC through induction of S-phase arrest and apoptosis via the PI3K/AKT/mTOR/p70S6K pathway.